A new Cangoderces (Araneae, Telemidae) from DR Congo, the first telemid from Central Africa - Jocqué, Rudy; Jocque, Merlijn; Mbende, Menard (Zootaxa, 2022)
Spiders collected as part of a rapid biodiversity survey in lowland forest in Democratic Republic Congo contained a new species of Cangoderces Harington, 1951 (Telemidae). The male of the new Cangoderces wewef sp. n. is characterized by the male palp with a deep triangular dorsal indentation of the bulbus and the apophyses at the base of the embolus. The female is recognized by the shape of the sclerotized spermatheca in the endogyne. The presence of the species in DR Congo fills the huge distribution gap between the species known from South Africa, Kenya and western Africa.